An introduction to solid state diffusion - Borg, R. J. (Richard John), 1925- (Academic Press, 1988)
The energetics and mechanisms of diffusion control the kinetics of such diverse phenomena as the fabrication of semiconductors and superconductors, the tempering of steel, geological metamorphism, the precipitation hardening of nonferrous alloys and corrosion of metals and alloys. This work explains the fundamentals of diffusion in the solid state at a level suitable for upper-level undergraduate and beginning graduate students in materials science, metallurgy, mineralogy, and solid state physics and chemistry. A knowledge of physical chemistry such as is generally provided by a one-year undergraduate course is a prerequisite, though no detailed knowledge of solid state physics or crystallography is required.